ANALISIS PENGARUH PRODUK, PERSONIL, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PT. MNET INDONESIA - Fitry Yani Herlina; Rusda Irawati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
This research is motivated by the needs of society and the conditions of service business competition intensifies, so the company must create a new marketing strategy to maintain and gain market share higher. As for the issue of this research is "What are the factors of products, personnel and promotion effect on customer satisfaction in PT. Mnet Indonesia ".The purpose of this study to determine how the product implementation process, personnel and promotion are being made to improve customer satisfaction and to determine the extent of the effect of products, personnel and promotion of customer satisfaction. The hypothesis of this study is the product, personnel and promotion effect on customer satisfaction. The author uses quantitative research methods explanatory. The research sample as many as 101 customers with a 99% confidence level (α = 0.01) in. Results of multiple linear regression analysis we concluded that all the independent variables, namely products, personnel and promotion have a positive effect on the dependent variable of customer satisfaction. Based on the results of the analysis of figures obtained correlation R of 0.697. This shows that there is a strong relationship or correlation between the products, personnel and promotion of customer satisfaction. While the results of the analysis of determination (R2) of 48.6%. This shows that the percentage of the effect of independent variables on the dependent variable of 48.6%. While the remaining 51.4% influenced or explained by other variables not included in this research model.